2013
DOI: 10.1113/jphysiol.2013.254193
|View full text |Cite
|
Sign up to set email alerts
|

Novel role for thioredoxin reductase‐2 in mitochondrial redox adaptations to obesogenic diet and exercise in heart and skeletal muscle

Abstract: Key points• For reasons not completely understood, obesogenic high-fat, high-sucrose (HFHS) diets and exercise training both increase free fatty acid utilization and chronic oxidative stress, yet the former is deleterious to cardiovascular/metabolic health, whereas the latter is beneficial.• Here, we report that the heart shows decreased mitochondrial H 2 O 2 (mH 2 O 2 ) generation following HFHS diet, while skeletal muscle shows increased mH 2 O 2 , and uncover a novel role for thioredoxin reductase-2 (TxnRd2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 53 publications
(59 reference statements)
3
70
0
Order By: Relevance
“…Increased protein levels of cardiac TrxR2 have been previously observed in mice on a high‐fat, high‐sugar diet (Fisher‐Wellman et al. 2013). In that study, the authors also uncovered the critical role played by this enzyme in suppressing mitochondrial H 2 O 2 emission, specifically during fatty acid oxidation (Fisher‐Wellman et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased protein levels of cardiac TrxR2 have been previously observed in mice on a high‐fat, high‐sugar diet (Fisher‐Wellman et al. 2013). In that study, the authors also uncovered the critical role played by this enzyme in suppressing mitochondrial H 2 O 2 emission, specifically during fatty acid oxidation (Fisher‐Wellman et al.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the authors also uncovered the critical role played by this enzyme in suppressing mitochondrial H 2 O 2 emission, specifically during fatty acid oxidation (Fisher‐Wellman et al. 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Long-term endurance exercise may potentially reduce ROS production due to systemic effects (improved insulin signaling, reduced inflammatory status, alteration of plasma lipids, and reduced activity of the reninangiotensin system), which may dampen the activation of ROS-producing enzymes. In addition, exercise training has also been reported to improve endogenous antioxidant capacity of the heart (17,20).…”
Section: Discussionmentioning
confidence: 99%
“…In this model, the increased concentration of H 2 O 2 induces the activation of c-Jun N-terminal kinase, which promotes the phosphorylation of the transcription factor family FOXO, leading to catalase overexpression (73). The capacity of rat hearts to counteract the oxidative stress caused by a chronic high-fat/ high-sugar diet by upregulating thioredoxin reductase-2 has been recently shown, although the signaling involved in this mechanism was not investigated (27). Conversely, other authors found an increased expression of the thioredoxin endogenous inhibitor named thioredoxin interacting protein, and therefore reduced anti-oxidant defenses, after hyperglycemia in patients with diabetes and in rodents with type I and II diabetes (16).…”
Section: Metabolic Alterations and Antioxidant Defensesmentioning
confidence: 99%